Innovative Strategy for Education in Digital Era - Kustinah Kustinah (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The writer of this paper believes that innovative strategy for education in digital era isreally needed , especially in teaching English. This paper focuses in how to use the internetfor teaching speaking and listening. The reason is people all around the world now use theinternet everyday for their various needs, Some use the internet for entertainment, businessor education.Talking about teaching speaking, a teacher or a lecturer can use the internet fordownloading splendid short educational videos with various topics as the teaching material.We can play the videos with various topics of conversation. Students are asked to watch thevideos by paying attention to how the native speakers pronounce the English wordsproperly. The teacher or the lecturer can deliver spontaneous questions about the videos.Without them realizing, students will have an exercise how to speak Englishnaturally.Another way is students can be asked to imitate for example, pronouncing newvocabularies or difficult words. The native speaksers in the video are playing roles asmodels for students to learn. By using short educational videos taken from the internet, ateaching and learning process will be more fun and interesting. Besides video, we can usethe internet to download films or songs. Because speaking skill relates to listening skill, wecan also train students’ ability in speaking by giving them a lot of practices in listening.After watching a film for instance, students are taught to retell certain dialogues from thefilm. We are also possibly to have a small discussion about the theme of the film. We candivide students in groups to discuss together. By doing so, students will practice bothspeaking and listening skill.About songs, students can be asked to write the lyric of thesongs that had been heard. We play the songs for several times and students will “guess”the lyric. From the lyric of a song, students can learn many vocabularies. New vocabulariesare essential in speaking. We see here that the internet can maximize a teaching andlearning process. We can use language laboratory to play the short videos and givequestions to all students. They will learn about different accent of spoken English toobecause sometimes the “player” in the videos come from various background. Some areAmerican, European or Afro-American. Internet has become “a friend” for everybody. Itcan be accessed from a cellphone instead of a laptop. It is easier for us to get many kinds ofinformation quickly. But in school or campus, the use of internet in a language laboratorywill be more effective.Keywords : innovative teaching strategy; the internet; video; song; teaching speaking and listening